2011
DOI: 10.1186/1740-3391-9-10
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between daylength and suicide in Finland

Abstract: BackgroundMany previous studies have documented seasonal variation in suicides globally. We re-assessed the seasonal variation of suicides in Finland and tried to relate it to the seasonal variation in daylength and ambient temperature and in the discrepancy between local time and solar time.MethodsThe daily data of all suicides from 1969 to 2003 in Finland (N = 43,393) were available. The calendar year was divided into twelve periods according to the length of daylight and the routinely changing time differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 51 publications
3
21
1
1
Order By: Relevance
“…However, on the basis of these data it cannot be judged whether the finding concerned only depressed suicide cases or is a key feature of depressive disorder in general. Nevertheless, it gives support to the view that the activation of brown adipose tissue improves cold tolerance at the cost of heat tolerance, triggering anxiety and psychomotor agitation and eventually affecting mood in a negative way during the late-spring and early summer [8].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…However, on the basis of these data it cannot be judged whether the finding concerned only depressed suicide cases or is a key feature of depressive disorder in general. Nevertheless, it gives support to the view that the activation of brown adipose tissue improves cold tolerance at the cost of heat tolerance, triggering anxiety and psychomotor agitation and eventually affecting mood in a negative way during the late-spring and early summer [8].…”
Section: Discussionmentioning
confidence: 85%
“…Suicide rates vary in both the short and long term [6][7][8]. Mortality from suicide may additionally vary considerably within a country [9] or in accordance with a section of the population [10].…”
Section: Introductionmentioning
confidence: 99%
“…PSG-assessed decreased sleep efficiency has also been associated with number of lifetime suicide attempts 10 . Other investigations have suggested that altered chronobiological activity is related to both suicidal thoughts 11 and deaths 12 . The EEG sleep literature and systematic investigations evaluating time of day effects on suicide risk are relatively sparse, however, and analyses often do not adjust for depressive symptoms or use current suicidal thoughts as an outcome measure.…”
Section: Introductionmentioning
confidence: 99%
“…В отличие от наших данных, например, в Фин-ляндии [11] единственный максимум суицидов при-ходится на период с 15 мая по 25 июля, т.е. он сим-метричен относительно летнего солнцестояния.…”
Section: анализ годового ритмаunclassified